PENGARUH AMBIANCE, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP INTENSI PEMBELIAN COFFEE SHOP (Studi Kasus Green Ease Coffee Jakarta Barat) - Sundoro, Christian (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study is to determine the effect of Ambiance, Service Quality, and Product Quality on Purchase Intention. The object of this research is Ease Coffee, West Jakarta. This study was conducted on 100 respondents with a quantitative descriptive approach. Therefore, the analysis of the data used is the Statistical Analysis of Multiple Linear Regression. The results of this study indicate that the t test of Ambiance, Service Quality, has a significant effect on Coffee Purchase Intention at Green Ease Coffee, West Jakarta, while Product Quality does not significantly influence Coffee Purchase Intention at Green Ease Coffee, West Jakarta.